Faktor Penghambat Penanganan Pencemaran Lingkungan Dalam Pengolahan Limbah Di Pt Royal Coconut Gorontalo - Mutawakkil Ibnu Arif; Mohamad Rusdiyanto U. Puluhulawa; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to provide a clear picture of the handling of criminal acts of environmental pollution in waste processing at PT Royal Coconut Gorontalo.This research uses empirical legal research methods. Empirical legal studies themselves are studies that view law as reality, including social reality, cultural reality, and empirical studies of the world. This research took place at the Environment and Forestry Service of Gorontalo Province. The results of this research show that: Handling criminal acts of environmental pollution in waste processing at PT Royal Coconut Gorontalo has not been handled properly and correctly. Good and correct handling has not been implemented due to internal factors such as communication, supervision, individual, financial and others, as well as external factors such as community factors, law enforcement, culture, advice and infrastructure. Ineffective handling can have an impact on society. Waste from processing is very dangerous when it pollutes residents' areas, the impact that can be felt by the community is contracting disease and can even cause death if it is not handled according to waste processing procedures. Law enforcement against environmental pollution which triggers criminal acts in Gorontalo Province has not been implemented properly. This is due to several factors that have not been fulfilled optimally. This can be seen from various factors such as law enforcement not being optimal in terms of a persuasive approach, inadequate facilities and infrastructure with limited human resources, as well as community habits and culture which consider environmental pollution to be a normal and common occurrence.